2022
DOI: 10.1021/acs.jced.2c00487
|View full text |Cite
|
Sign up to set email alerts
|

Mutual and Thermal Diffusivities in Mixtures of Cyclohexane, n-Hexadecane, n-Octacosane, or n-Hexanoic Acid with Carbon Dioxide Obtained by Dynamic Light Scattering and Molecular Dynamics Simulations

Abstract: The present work reports Fick diffusion coefficients D 11 in the saturated liquid phases of binary mixtures of cyclohexane, n-hexadecane, noctacosane, or n-hexanoic acid and dissolved carbon dioxide (CO 2 ) as a function of composition. D 11 is experimentally determined by dynamic light scattering (DLS) and predicted by equilibrium molecular dynamics (EMD) simulations within or close to saturation conditions at temperatures between 303 and 423 K and CO 2 mole fractions x CO2 up to 0.99. Thermal diffusivity dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 101 publications
13
27
0
Order By: Relevance
“…Furthermore, the AARD of 7.7% of D self,1 from EMD simulations from the T-dependent Arrhenius-type fits of the experimental DLS data for the C 6 H 12 -based systems shows that the FF modification for C 6 H 12 proposed in our previous work is transferable. 38 In agreement with previous experimental investigations of binary mixtures consisting of a liquid and a dissolved gas close to infinite dilution, a generally decreases with increasing T within uncertainties and no distinct effect of p or the amount or type of the dissolved gas on a was found for the systems studied in this work. Until now, for most of the solvent−solute combinations investigated in previous studies, systems composed of molecules exhibiting larger molar mass showed a smaller D 11 value at a given T. In contrast, D 11 The semiempirical prediction model of Wu et al, 9 which was developed in connection with n-alkane-and 1-alcoholbased mixtures with dissolved gases at the beginning of this project, can predict D 11 in mixtures based on C 6 H 12 well even if a refrigerant like R143a is dissolved.…”
Section: ■ Conclusionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the AARD of 7.7% of D self,1 from EMD simulations from the T-dependent Arrhenius-type fits of the experimental DLS data for the C 6 H 12 -based systems shows that the FF modification for C 6 H 12 proposed in our previous work is transferable. 38 In agreement with previous experimental investigations of binary mixtures consisting of a liquid and a dissolved gas close to infinite dilution, a generally decreases with increasing T within uncertainties and no distinct effect of p or the amount or type of the dissolved gas on a was found for the systems studied in this work. Until now, for most of the solvent−solute combinations investigated in previous studies, systems composed of molecules exhibiting larger molar mass showed a smaller D 11 value at a given T. In contrast, D 11 The semiempirical prediction model of Wu et al, 9 which was developed in connection with n-alkane-and 1-alcoholbased mixtures with dissolved gases at the beginning of this project, can predict D 11 in mixtures based on C 6 H 12 well even if a refrigerant like R143a is dissolved.…”
Section: ■ Conclusionsupporting
confidence: 92%
“…Except for the eth-C 6 H 12 O 2 + R143a system, which is constantly underpredicted, the EMD simulations are able to reproduce the experimental data in a purely predictive manner. Furthermore, the AARD of 7.7% of D self,1 from EMD simulations from the T -dependent Arrhenius-type fits of the experimental DLS data for the C 6 H 12 -based systems shows that the FF modification for C 6 H 12 proposed in our previous work is transferable …”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…The present study is connected with investigations on how the characteristics of the involved molecules affect diffusion in the saturated liquid phase(s) of binary systems consisting of gases dissolved in liquids in vapor–liquid or vapor–liquid–liquid equilibrium (VLE or VLLE). In this context, binary systems consisting of carbon dioxide (CO 2 ) combined with n -hexane (C 6 H 14 ), cyclohexane, n -hexadecane, n -octacosane, n -hexanoic acid, or 1-hexanol (C 6 H 14 O) over a wide concentration range were investigated using dynamic light scattering (DLS) combined with Raman spectroscopy (RS) and equilibrium molecular dynamics simulations. These studies allowed to examine the impact of varying alkyl chain length as well as of different functional groups for hydrocarbons with the same number of carbon atoms on the phase behavior and Fick diffusion coefficient D 11 .…”
Section: Introductionmentioning
confidence: 99%